Analisa Sifat Kemagnetan Polimer Poliethylen Glycol (PEG-4000)-coated Nanopartikel Magnetite Fe3O4 Menggunakan Vibrating Sample Magnetometer (VSM) - Alfrie Musa Rampengan; Soenandar Milian Tompunu Tengker (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Iron oxide (Fe3O4) nanoparticles have been synthesized using coprecipitation method. Characterization of the magnetic properties of iron oxide (Fe3O4) nanoparticles using Transmission Electron Microscopy (TEM) shows a loop hysteresis curve on Fe3O4 magnetite nanoparticles with a value of Mr 7.7 emu/g at 0 kOe field, Ms 68.2 emu/g at an external field 14 ,61 kOe. A low Mr value or close to zero indicates that the Fe3O4 nanoparticle material is softmagnetic. Fe3O4 nanoparticles that had been modified with PEG-4000 polymer showed a Ms value of 55.7 emu/g in a 14 kOe field, an Hc coercivity field of about 60 Oe, and a Mr. 6.3 emu/g value in a 0 kOe field. The smaller the particle size, the more likely the material has a single magnetic domain. The smaller the sample particle size, the smaller the remanent magnetization value. The smaller the value of remanent magnetization, the residual magnetization that is still possessed by a material/sample when it is not affected by an external magnetic field is also greater.